Polygraph analyses: technical and practical background - Winkler-Galicki, Jakub; Bartkowiak-Wieczorek, Joanna; Synowiec, Dominik; Dąbrowska, Renata; Mądry, Edyta (Journal of Medical Science, 2022)
A lie is not the truth, a common definition found in each dictionary or encyclopaedia. Humans use it in different situations and for various reasons, but in the case of forensics, recruitment, and trust in the company or family, it can be curtailed in order to avoid it or to detect it. One of the possible detection tools is the polygraph, whereby lies may be registered and interpreted by means of physiological activities controlled by the autonomic nervous system, such as sweating, trembling, or changes in breathing or in the heart rate. The analyses of the aforementioned parameters are monitored in response to questions, thus, providing information about a possible lie. Questions should be asked according to one of the approved protocols and given procedures and algorithms, which are constantly developed and revised to provide the best possible results.
Keywords: polygraph; lie detection; autonomic nervous system